2022
DOI: 10.1039/d1dt03687d
|View full text |Cite
|
Sign up to set email alerts
|

LaTiO2N nanopowders (NPs) with low surface defect density via nitridation of flame made NPs retaining simple perovskite structure

Abstract: LaTiO2N NP synthesized from flame made LaTiO3 NP exhibits less absorption background above the optical absorption edge than that synthesized from flame made La2Ti2O7 NP, suggesting a low surface defect density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested that the defects play a pivotal role in governing the photocatalytic performance of LaTiO 2 N. , The types of defects in LaTiO 2 N, their locations, energy states, concentrations, etc., correlate intrinsically with the behavior of photocarriers (e – and h + ). For instance, a variety of crystal defects have been identified in conventionally prepared LaTiO 2 N, including stacking faults, coherent low-angle domain boundaries, oxygen-rich planes, twin domains, grain boundaries, surface reconstruction layers, ,, various point defects [e.g., Ti 3+ , oxygen vacancies (V O ), nitrogen vacancies (V N ), and oxygen at nitrogen sites (O N )], ,,, etc. These defects, particularly when they are located in the bulk, are detrimental to photocatalytic activity as they can retard the movement of photocarriers and trigger unproductive photocarrier recombination .…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested that the defects play a pivotal role in governing the photocatalytic performance of LaTiO 2 N. , The types of defects in LaTiO 2 N, their locations, energy states, concentrations, etc., correlate intrinsically with the behavior of photocarriers (e – and h + ). For instance, a variety of crystal defects have been identified in conventionally prepared LaTiO 2 N, including stacking faults, coherent low-angle domain boundaries, oxygen-rich planes, twin domains, grain boundaries, surface reconstruction layers, ,, various point defects [e.g., Ti 3+ , oxygen vacancies (V O ), nitrogen vacancies (V N ), and oxygen at nitrogen sites (O N )], ,,, etc. These defects, particularly when they are located in the bulk, are detrimental to photocatalytic activity as they can retard the movement of photocarriers and trigger unproductive photocarrier recombination .…”
Section: Introductionmentioning
confidence: 99%